A semi-analytical approach on critical thermal states in water wall tubes of a subcritical drum boiler of a thermal power plant. (1st December 2021) - Assefinejad, A.H.; Kermanpur, A.; Eslami, A.M.
Abstract: One of the most important issues in design of water tube boilers is the prediction of the critical heat flux and the corresponding critical quality of the steam and vice versa. This phenomenon directly affects growth rate of oxide/deposit layers, rising water wall tubes temperature, and consequently tubes burnout. In the present work, the critical situations in a furnace of a subcritical drum boiler were investigated. It was shown that by moving to higher altitudes of the investigated furnace, its water wall tubes were more sensitive to heat flux distribution, which consequently increased the possibility of dryness phenomenon and failure of the tubes. Besides, this study demonstrated that in the event of a disturbance in the fluid flow inside the tubes, all the length of water wall tube are at serious risk of burning and overheating. Microstructural evolutions, existence of thick deposits, and frequent failures at higher the altitudes confirmed the semi-analytical results. Highlights: The critical heat flux in a furnace of a subcritical drum boiler was investigated. The water wall tubes in higher altitudes were more sensitive to heat flux distribution. The possibility of dryness and failure of the tubes increased with increasing altitude. Serious risk of overheating occurs in the whole tube length by fluid flow disturbance.